What Happened Next? The Experiences of Postsecondary Students With Disabilities as Colleges and Universities Reconvened During the Pandemic - Madaus, Joseph W.; Faggella-Luby, Michael N.; Dukes, Lyman L.; Gelbar, Nicholas W.; Langdon, Shannon; Tarconish, Emily J.; Taconet, Ashely (Frontiers in Psychology, 2022)
COVID-19 caused nearly every college and university in the United States to rapidly shift to remote learning during the spring 2020 semester. While this impacted all students to different degrees, students with disabilities (SWD) faced new challenges related to their mental health, the accessibility of their instruction, the receipt of accommodations, and their interactions with faculty and student support personnel. Literature is emerging that describes the experiences of SWD during the spring 2020 semester and the swift change to remote learning. However, little is currently known about what followed for these students. The present study builds from a prior investigation of SWD during the spring 2020 semester and examines student experiences and perceptions during the 2020-2021 academic year. Eighty-eight SWD from colleges across the United States completed an instrument that contained a mix of demographic, yes/no, Likert scale and open-ended items. Responses revealed most items related to accessing services and instruction showed no improvement from the spring 2020 semester, and that items related to mental health, motivation to learn, and connections with peers were perceived as worse than in spring 2020. Open-ended responses revealed similar themes, with some students describing no improvements, and others noting that accessibility service offices and faculty provided enhanced methods of communication and support. Implications for practice and future research are presented.